2017
DOI: 10.33225/pec/17.75.612
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Computer-Based National Examination in Indonesian Schools: The Challenges and Strategies

Abstract: In line with technological development, the computer-based national examination (CBNE) has become an urgent matter as its implementation faces various challenges, especially in developing countries. Strategies in implementing CBNE are thus needed to face the challenges. The aim of this research was to analyse the challenges and strategies of Indonesian schools in implementing CBNE. This research was qualitative phenomenological in nature. The data were collected through a questionnaire and a focus group discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…Every educational policy has its advantages and challenges [14]. If the benefits are greater and urgent, various challenges will be assessed to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Every educational policy has its advantages and challenges [14]. If the benefits are greater and urgent, various challenges will be assessed to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang fokus pada implementasi UNBK telah banyak dilakukan (Aden, Basir, & Kusdaniyama, 2020;Firmansyah, 2018;Harmiyuni & Sailan, 2016;Hartina, 2018;Meita & Fatoni, 2020;Murtadlo, Jazuli, & Catur Murti, 2019;Pakpahan, 2016;Pernamawati, Kritiawan, & Fitria, 2021;Tamala, 2019). Penelitian sebelumnya telah mengangkat berbagai isu, termasuk bagaimana pelaksanaan UNBK (Pernamawati, dkk., 2021;Simbolon, Kadir, & Nasution, 2019), kesiapan pelaksanaan ujian nasional berbasis komputer bagi sekolah dan siswa (Meita & Fatoni, 2020), strategi kepala sekolah dalam meningkatkan kualitas guru dan siswa untuk jenis soal UNBK (Negara, Santosa, & Bahri, 2017;Nirmala, 2013;Sampebua & Membala, 2018), manfaat dan tantangan dalam berbagai model UNBK (Pakpahan, 2016;Rahmania, Budiono, Soenaryo, Syakur, & Tinus, 2020;Retnawati, Hadi, Nugraha, Arlinwibowo, Sulistyaningsih, Djidu, Apino, & Iryanti, 2017)), dan evaluasi pelaksanaan UNBK (Pernamawati, dkk., 2021;Rusmawati, Suryana, & Harapan, 2020). Akan tetapi, penelitian yang fokus menginvestigasi strategi yang dilakukan kepala sekolah dalam pelaksanaan UNBK di sekolah masih kurang dieksplorasi (lihat Tamala, 2019).…”
Section: Pendahuluanunclassified
“…In terms of information and communication, correspondence and administration, as well as testing, digitization has been carried out for the past few years. A number of studies such as Retnawati et al [9], Alifiani et al [10], have reported how the constraints and efficacy of digitization of education on these aspects. However, digitization in the aspect of learning is still not popularly implemented both at the higher education level, especially in primary and secondary education.…”
Section: Introductionmentioning
confidence: 99%